Islam and violence - Mohammed, Khaleel (Cambridge elements Elements in religion and violence, 2019)
After 9/11, many writers have posited that the relationship between Islam and violence is either elemental or anomalous. Khaleel Mohammed describes Islam as transcending the usual understanding of religion, being instead like a "sacred canopy" that provides meaning for every apsect of life. In addition, he shows that violence has both physical and psychological dimensions and expounds at length on jihad. He traces the term's metamorphosis of meaning from a struggle in any worthy cause to war and to its present-day extension to include martyrdom and terrorism. Finally, he covers the dimensions of violence in Islamic law and institutional patriarchy--back cover